A PRISMA Systematic Review of AISAS Model Implementation to Enhance User Engagement on Instagram (2015–2025) - Ressa Uli Patrissia (Dinasti Publisher, 2025)
This study presents a systematic synthesis of research on the implementation of the AISAS (Attention, Interest, Search, Action, Share) model to enhance user engagement on Instagram from 2015 to 2025. Using the PRISMA 2020 protocol, 58 scholarly articles were analyzed to identify thematic patterns, best practices, and research gaps. The findings confirm that AISAS has been widely applied in influencer marketing, visual content strategies, brand awareness campaigns, and user-generated content, et the Search and Share stages remain underexplored. The study contributes a key novelty by proposing the Adaptive AISAS Cycle (AAC), which reconceptualizes AISAS not as a linear funnel but as a recursive engagement loop, where Search renews Attention and Share reinforces Interest. This cyclical interpretation better reflects the iterative dynamics of digital consumer behavior shaped by algorithmic personalization, emotional storytelling, and participatory culture. Theoretically, this study enriches digital marketing literature by advancing AISAS into an adaptive cycle, while practically it provides guidance for designing Instagram strategies that sustain long-term engagement and brand advocacy.